Streetlights Disrupt Night-Time Sleep in Urban Black Swans - Aulsebrook, Anne E.; Lesku, John A.; Mulder, Raoul A.; Goymann, Wolfgang; Vyssotski, Alexei L.; Jones, Therésa M. (Frontiers in Ecology and Evolution, 2020)
Artificial light at night could have widespread and detrimental impacts on sleep. To reduce disruptive effects of artificial light on sleep in humans, most smartphones and computers now have software that reduces blue light emissions at night. Little is known about whether reducing blue light emissions from city lights could also benefit urban wildlife. We investigated the effects of blue-rich (white) and blue-reduced (amber) LED streetlights on accelerometry-defined rest, electrophysiologically-identified sleep, and plasma melatonin in a diurnal bird, the black swan (Cygnus atratus). Urban swans were exposed to 20 full nights of each lighting type in an outdoor, naturalistic environment. Contrary to our predictions, we found that night-time rest was similar during exposure to amber and white lights but decreased under amber lights compared with dark conditions. By recording brain activity in a subset of swans, we also demonstrated that resting birds were almost always asleep, so amber light also reduced sleep at night. We found no effect of light treatment on total (24 h) daily rest or plasma melatonin. Our study provides the first electrophysiologically-verified evidence for effects of streetlights on sleep in an urban animal, and furthermore suggests that reducing blue wavelengths of light might not mitigate these effects.